2021
DOI: 10.1088/1752-7163/abd28d
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-18 and carbon-13 isotopes in eCO2 and erythrocytes carbonic anhydrase activity of Finnish prediabetic population

Abstract: Complex human physiological processes create the stable isotopic composition of exhaled carbon dioxide (eCO2), measurable with noninvasive breath tests. Recently, isotope-selective breath tests utilizing natural fluctuation in 18O/16O isotope ratio in eCO2 have been proposed for screening prediabetic (PD) individuals. It has been suggested that 18O/16O fractionation patterns reflect shifts in the activity of carbonic anhydrase (CA), an enzyme involved in the metabolic changes in the PD state. To evaluate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It has been suggested that (pre)diabetic patients have an altered carbonic anhydrase activity, causing a change in CO 2 -water oxygen equilibration in tissues and thus a specific δ 18 O value in exhaled CO 2 [18]. This remains controversial since no highly significant difference was found in another study [43]. An interesting study has nevertheless shown a link between respired CO 2 and systemic inflammation [32].…”
Section: Metabolic Diseases and Isotope Composition Of Respired Comentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that (pre)diabetic patients have an altered carbonic anhydrase activity, causing a change in CO 2 -water oxygen equilibration in tissues and thus a specific δ 18 O value in exhaled CO 2 [18]. This remains controversial since no highly significant difference was found in another study [43]. An interesting study has nevertheless shown a link between respired CO 2 and systemic inflammation [32].…”
Section: Metabolic Diseases and Isotope Composition Of Respired Comentioning
confidence: 97%
“…Noteworthy, isotopic variations also likely come from differences in country-specific food intake behaviour and thus how patients with diabetes and metabolic syndrome readjust their diet. Still, there is no specific δ 13 C signature of exhaled breath CO 2 in (pre)diabetic patients [18,43]. It has been suggested that (pre)diabetic patients have an altered carbonic anhydrase activity, causing a change in CO 2 -water oxygen equilibration in tissues and thus a specific δ 18 O value in exhaled CO 2 [18].…”
Section: Metabolic Diseases and Isotope Composition Of Respired Comentioning
confidence: 99%